2010
DOI: 10.1002/ijc.25600
|View full text |Cite
|
Sign up to set email alerts
|

VEGF stimulates PKD‐mediated CREB‐dependent orphan nuclear receptor Nurr1 expression: Role in VEGF‐induced angiogenesis

Abstract: New vessel formation is critical for solid tumor growth and it is primarily stimulated by the most potent angiogenic factor vascular endothelial growth factor (VEGF or VEGF-A165). VEGF promotes endothelial cell proliferation by initiating signaling cascades to increase gene transcription. Recent works showed that VEGF potently and rapidly induces expression of orphan nuclear receptor Nurr1 in endothelial cells. However, the signaling pathway for VEGF-induced Nurr1 expression and its role in VEGF-induced endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…Indeed, gremlin causes CREB activation, nuclear translocation, and DNA binding in ECs through a productive gremlin-VEGFR2 interaction. PI-3K and PKC mediate CREB activation after VEGFR2 engagement by 17 Our observations demonstrate a nonredundant role of VEGFR2-mediated mitogen activated protein kinase and Src signaling in CREB activation by gremlin, whereas no effect was exerted by the PI-3K inhibitors LY294002 and Wortmannin or the PKC inhibitor GF109203X (data not shown). Together with the different kinetics of CREB activation by the 2 factors, these data reveal the previously unrecognized capacity of gremlin to trigger VEGFR2-dependent intracellular events distinct from those elicited by VEGF-A.…”
mentioning
confidence: 68%
“…Indeed, gremlin causes CREB activation, nuclear translocation, and DNA binding in ECs through a productive gremlin-VEGFR2 interaction. PI-3K and PKC mediate CREB activation after VEGFR2 engagement by 17 Our observations demonstrate a nonredundant role of VEGFR2-mediated mitogen activated protein kinase and Src signaling in CREB activation by gremlin, whereas no effect was exerted by the PI-3K inhibitors LY294002 and Wortmannin or the PKC inhibitor GF109203X (data not shown). Together with the different kinetics of CREB activation by the 2 factors, these data reveal the previously unrecognized capacity of gremlin to trigger VEGFR2-dependent intracellular events distinct from those elicited by VEGF-A.…”
mentioning
confidence: 68%
“…NR4A receptors are downstream targets of VEGF, promoting proliferation of endothelial cells in vitro and in vivo (25,28). Transcription of NR4A receptors is increased by VEGF, hypoxia, and CREB activation in vascular endothelial cells (25).…”
Section: Metabolism and Angiogenesismentioning
confidence: 99%
“…Transcription of NR4A receptors is increased by VEGF, hypoxia, and CREB activation in vascular endothelial cells (25). In vivo, the transcriptional activity of NR4A1 and NR4A2 is involved in VEGF-mediated angiogenesis (28,29).…”
Section: Metabolism and Angiogenesismentioning
confidence: 99%
“…PKD directly phosphorylates the transcription factor CREB to allow recruitment of coactivators, including CREB binding protein (CBP)/p300, and augment CREB-mediated gene expression (26). In a recent study, CREB dependent transcription of the immediate-early gene, Nurr1, was found to be important for in vivo angiogenesis in a mouse model using matrigel plugs (27). Furthermore, PKD can also phosphorylate several members of the Class IIa histone deacetylase (HDAC) family, notably HDAC5 and HDAC7 (10,28,29).…”
Section: Pkd Function In Endothelial Cellsmentioning
confidence: 99%